Healthy aging? An evaluation of sport participation as a resource for older adults in retirement. (1st January 2019) - Walsh, David W.; Green, B. Christine; Holahan, Carole; Cance, Jessica D.; Lee, Don
Abstract: Growing disparities between quality and quantity of life may be one of the most significant health challenges of our time. Retirement is a significant transitional event that can impact quality of life outcomes. Drawing on the Resource-Based Dynamic Perspective Theory, successful adaptation from the retirement transition is dependent upon resources known to predict retirement well-being. The purpose of this study was to evaluate the relationship between sport participation and these resources. Data from surveys of two retirement communities in southeast Texas were collected ( N = 373). Structural equation modeling was used to analyze the relationships between sport participation, resources, and retirement well-being. Findings from this research provide empirical evidence to support participation in sport as a positive influencer of resources in retirement, assisting continued human development as people age. Further, the concept of sport embeddedness, which describes people's beliefs, social involvement, and behavioral involvement with sport, is advanced.